Facile preparation of yellow and red emitting ZnCdSeS quantum dots and their third-order nonlinear optical properties. (September 2018) - Moslemi, Z.; Soheyli, E.; Majles Ara, M.H.; Sahraei, R.
Abstract: In this study, N-acetyl-l -cysteine-capped quaternary ZnCdSeS quantum dots (QDs) were prepared using a colloidal method in two different structures, which we refer to as ZnCdSeS-yellow and ZnCdSeS-red QDs. These high quality QDs were synthesized directly in aqueous solution with two different amounts of the selenium precursor. The structural and optical properties of the ZnCdSeS QDs were studied to determine the compositions of the QDs and their composition-dependent absorption and emission characteristics. Regardless of the composition of the QDs, transmission electron microscopy measurements demonstrated that both quaternary QDs were similar in size with narrow size distributions. Using a continuous wave (CW) He-Ne laser at 632.8 nm, the linear absorption coefficients were calculated for each sample as approximately 7.55 × 10 1 and 8.99 × 10 1  m −1 for the ZnCdSeS-yellow and ZnCdSeS-red QDs, respectively. The magnitudes and signs of the third-order nonlinear refractive indices ( n 2 ) as well as the nonlinear absorption coefficients ( β ) were determined for the as-prepared QDs based on the closed and open aperture Z-scan at different intensities. The results indicated positive signs of n 2 for both the ZnCdSeS QDs, thereby demonstrating the self-focusing effect in both QDs. The nonlinear susceptibility ( χ (3) ) values were also determined for the alloyed QDs. The n 2, β, and χ (3) values for the QDs were in the orders of 10 −12  m 2  W −1, 10 −4  mW −1, and 10 −14 SI, respectively. Our results indicate that ZnCdSeS alloyed QDs are satisfactory candidate for use in nonlinear optical devices because of their intrinsic nonlinear and tunable emission properties. Highlights: High quality/emissive ZnCdSeS quantum dots (QDs) successfully prepared. Variation in Se concentration led to significant shift in emission color. Structural and optical properties of the ZnCdSeS QDs characterized. n 2, β, and χ (3) determined using a 632.8-nm CW He-Ne laser and Z-scan method. Value of n 2 slightly larger for ZnCdSeS-yellow QDs than ZnCdSeS-red QDs. Z-scan indicated self-focusing effect and two-photon absorption process.